Macro and Micro Perspectives of Growth and Poverty in Africa - Christiaensen, Luc; Demery, Lionel; Paternostro, Stefano (Washington, DC: World Bank, 2014)
This article reviews trends in poverty, economic policies, and growth in a sample of African countries during the 1990s, drawing on the better household data now available. Experiences have varied. Some countries have seen sharp drops in income poverty, whereas others have witnessed marked increases. In some countries overall economic growth has been pro-poor and in others not. But the aggregate numbers hide systematic distributional effects. Taking both macro and micro perspectives of growth and poverty in Africa, the article draws four key conclusions. First, economic policy reforms (improving macroeconomic balances and liberalizing markets) appear conducive to reducing poverty. Second, market connectedness is crucial to enable participation in the gains from economic growth. Some regions and households by virtue of their remoteness were left behind when growth picked up. Third, education and access to land emerge as key private endowments to help households benefit from new economic opportunities. Finally, rainfall variations and ill health have profound effects on poverty outcomes, underscoring the significance of social risk management in poverty reduction strategies in Africa.